A acurácia da Escala de Experiência Sexual do Arizona (ASEX) para identificar disfunção sexual em pacientes do espectro da esquizofrenia - Nunes, Luciana Vargas Alves [UNIFESP] (2009)
Background: sexual dysfunction is frequent in patients with schizophrenia, it is reported as one of the most distressing antipsychotic’s adverse effects and it is directly related to treatment compliance. Objective: a) to assess the frequency of sexual dysfunction in a sample of outpatients with schizophrenia and schizoaffective disorder under antipsychotic therapy; b) to investigate the effect of different antipsychotics on sexual function; and c) to evaluate the accuracy of the Arizona Sexual Experience Scale (ASEX) to identify sexual dysfunction. Method: Outpatients with schizophrenia or schizoaffective disorder were asked to fulfill both the ASEX and the Dickson Glazer Scale for the Assessment of Sexual Functioning Inventory (DGSFi) at a single interview. Results: 137 patients were interwied. The sensitivity and specificity of the ASEX in relation to DGSFi were: 80.8%, (95% CI= 70.0%-88.5%) and 88.1% (95% CI= 76.5%-94.7%), and the misclassification rate was 9.5%. The ROC curve comparing the ASEX and the DGSFi scores revealed a value of 0.93 (CI= 0.879-0.970), with the optimum cut-off point of ASEX being 14/15. Sexual dysfunction measured was higher in females (79.2%) than in males (33.3%) (2 = 27.41, d.f.=1, p<0.001). Discussion: Patients under antipsychotic treatment showed a high level of sexual complaints, and the ASEX proved to be an accurate instrument to identify sexual dysfunction in an outpatient sample of patients with schizophrenia spectrum. Females showed a higher frequency of sexual dysfunctions and sexual drive and ability to reach orgasm were the most affected areas. The use of antipsychotics, especially the combinations, was more likely to impair sexual functioning.